2003
DOI: 10.2174/1381612033391748
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Oocyte Maturation, Ovulation, Fertilization, Cleavage and Implantation: A little dabll do ya

Abstract: Nitric oxide synthases, the enzymes that generate NO gas, may be involved in reproduction and development of multicellular organisms at many levels and thus provide important targets for design of drugs to intervene in reproductive processes. This review focuses on the role of nitric oxide in key events of reproduction including gamete activation, fertilization, early cell divisions and implantation. A general trend highlighted by the studies reviewed is that NO plays a biphasic role in reproduction. That is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…Later studies with Nos2-and Nos3-knockout mice showed that disruption of NOS2 had no effect on ovulation rate in superovulated prepubertal females; on the other hand, NOS3 deficiency had a significant negative effect (Hefler & Gregg 2002). Our results reinforce these studies, with the added value of being performed in non-stimulated cycles in mature females (a more physiological approach, since we cannot discard interactions between NO, NOS, and exogenous gonadotropins as indicated by Thaler & Epel (2003)). Current data, hence, support the hypothesis of Gregg (2003) about the role of Nos3 as an important modulator of ovulatory efficiency in mouse.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Later studies with Nos2-and Nos3-knockout mice showed that disruption of NOS2 had no effect on ovulation rate in superovulated prepubertal females; on the other hand, NOS3 deficiency had a significant negative effect (Hefler & Gregg 2002). Our results reinforce these studies, with the added value of being performed in non-stimulated cycles in mature females (a more physiological approach, since we cannot discard interactions between NO, NOS, and exogenous gonadotropins as indicated by Thaler & Epel (2003)). Current data, hence, support the hypothesis of Gregg (2003) about the role of Nos3 as an important modulator of ovulatory efficiency in mouse.…”
Section: Discussionsupporting
confidence: 78%
“…The effects of NOS3 deficiencies in ovulation may be mediated by changes in follicle development (Jablonka-Shariff et al 1999, Tempfer et al 2000, in the preovulatory LH surge (McCann et al 2003), and/or the ovulatory process by itself (Thaler & Epel 2003). Thaler & Epel (2003), revising many previous studies, suggest a model in which the preovulatory LH surge induces follicle cells to activate NOS; NOS induces production of NO, which stimulates synthesis of prostaglandins PGE 2 and PGF 2a and, thus, ovulation.…”
Section: Nos3 In Reproduction and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, simultaneous measurements of [Ca 2+ ] i and ΔΨ m revealed mitochondrial activation took place slightly earlier than ΔNO, suggesting that mitochondria may be responsible for ΔNO. ΔNO has generally been considered to be produced by cytosolic NO synthase (NOS) (Thaler and Epel 2003 ). Our data suggest that mitochondria may have their own separate generation system of NO such as mitochondrial NOS, mtNOS (Finocchietto et al 2009 ).…”
Section: Resultsmentioning
confidence: 77%